The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ani10030514
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Inflammatory Response to Exogenous LPS Challenge is Exacerbated in Broilers with Fatty Liver Disease

Abstract: This study aimed to examine hepatic function and inflammatory response in broilers with fatty livers, following acute lipopolysaccharide (LPS) challenge. One-day-old Lihua yellow broilers were fed a basal diet. Broilers were divided into four groups: control (CON), corticosterone treatment (CORT), LPS treatment (LPS), and LPS and CORT treatment (LPS&CORT). Results show that CORT induced an increase in plasma and liver triglycerides (TGs), which were accompanied by severe hepatic steatosis. The LPS group sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
3
10
0
Order By: Relevance
“…From the molecular point of view, the mRNA expression of IL-1β, IL-6, TNF-α, COX-2, and iNOS was significantly increased in the liver of LPS-challenged broilers, which was consistent with enhanced mRNA expression of TLR4. Our results were in accordance with the report of Mei et al (2020) in which LPS increased the mRNA expression of NF-κB, IL-1β, IL-6, IFN-γ, and iNOS in the liver of broilers. Similar results were observed by Li et al (2015) and Liu et al (2015).…”
Section: P-valuesupporting
confidence: 93%
See 1 more Smart Citation
“…From the molecular point of view, the mRNA expression of IL-1β, IL-6, TNF-α, COX-2, and iNOS was significantly increased in the liver of LPS-challenged broilers, which was consistent with enhanced mRNA expression of TLR4. Our results were in accordance with the report of Mei et al (2020) in which LPS increased the mRNA expression of NF-κB, IL-1β, IL-6, IFN-γ, and iNOS in the liver of broilers. Similar results were observed by Li et al (2015) and Liu et al (2015).…”
Section: P-valuesupporting
confidence: 93%
“…Also, this study found that supplementation with taurine could alleviate the inhibition of the ADG of the LPS-challenged broilers, indicating that taurine may exert a protective effect on the growth as evidenced by an increase in ADG of broilers under immunological stress. Moreover, many studies have shown that LPS administration causes liver injury and dysfunction in broilers (Morris et al, 2014;Qu et al, 2019;Jangra et al, 2020;Mei et al, 2020). The activities of AST and ALT in the serum are usually used clinically Means within the same row with no common superscript differ significantly (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Microbial infection is considered as a significant threat to animal production and food safety. Lipopolysaccharide (LPS), a membrane glycolipid, is a key component of gram-negative bacterial cell membrane and drives diseases (11). Animals are highly sensitive to the toxic effects of LPS.…”
Section: Introductionmentioning
confidence: 99%
“…Samples were rated based on the severity of steatosis, and graded 0-4, indicating none, slight, mild, moderate, and severe, respectively. Steatosis scores were analyzed independently by three veterinarians with reference to a previous publication [8]. In each case, ve tissue sections were examined and a numerical score was assigned.…”
Section: Histopathologymentioning
confidence: 99%
“…Glucocorticoid hormones (GCs) are important regulators of lipid metabolism, promoting lipogenesis when treated with chronic exposure [5].For instance, chronic excessive GCs exposure induced whole-body insulin resistance, strongly related to metabolic dysfunction including intrahepatic lipid accumulation, intramuscular fat deposition and abdominal adiposity in humans [6,7].Corticosterone (CORT) is the main active form of GC in chickens. Previous studies have shown that fatty liver disease can be induced by excessive CORT exposure in broilers [8][9][10].…”
Section: Introductionmentioning
confidence: 99%